(untitled) (Research, Society and Development, 2022)
The whitefly (Bemisia tabaci) is a phytophagous insect that is difficult to control and can cause great damage to several crops of economic importance, such as kale, being considered one of the most invasive species in the world. This work aimed to evaluate the insecticidal potential of the aqueous extract of the timbó root (Deguelia amazonica) in three modes of action (contact, translaminar and systemic) on whitefly nymphs in kale (Brassica oleraceae var. acephala). The botanical material collected was dried and crushed to obtain plant powder and preparation of aqueous extracts (plant powder + water). In order to set up the bioassays, induced whitefly infestations were performed on healthy kale seedlings. The extracts were applied on the nymphs to assess their nymphicidal potential and the LC50, which was 2.12%, and this concentration was used in the experiments on modes of action. The experimental design used was completely randomized. Mortality percentages were confirmed by ANOVA and means detected by Tukey’s test (p<0.05). The topical mode of action showed the best result (60.34%), being more than 30% above the second, which was systemic. However, the result via systemic action is also considered promising, exceeding 40% of nymphal mortality. The translaminar mode of action did not show significant results. Such results demonstrate the potential of timbó (D. amazonica) as an alternative control for the whitefly, presenting itself as a possibility in the rotation of natural products and commercial chemicals, being compatible with the proposal of integrated pest management in agroecological systems.